STRATEGI PERENCANAAN PENGEMBANGANOBYEK PARIWISATA KOTA PROBOLINGGO ( Studi Kasus Pada Taman Wisata Studi Lingkungan Kota Probolinggo ) - Astuti, Veronica Sri; Maksin, Mastina; Maharani Putri, Vero (Jurnal Sosial Humaniora Sigli, 2025)
This study aims to analyze the development planning strategy of the Environmental Study Tourism Park (TWSL) in Probolinggo City using six indicators of tourism development strategy according to Suwantoro (2015), namely: promotion, accessibility, tourist areas, types of tourist attractions, tourist products, and human resources. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the management of TWSL has progressed in terms of cleanliness, infrastructure, and environmental education. One of the leading programs, namely "Adek Dewa PLH", provides educational services to visitors, especially students, through interactive activities such as animal feeding, storytelling, and recycling activities. Organic waste management has also been carried out sustainably, where leaves and animal waste are recycled into compost as part of environmental conservation practices. However, this study also identified several obstacles, such as lack of directions to the location, weak digital promotion, budget constraints, lack of synergy between government agencies, and low community participation. Thus, the future TWSL development strategy needs to be directed more holistically and integrated. Short-term planning should focus on improving navigation and promotion, while medium- and long-term planning should include community empowerment, cross-sector partnerships, and regional expansion. Continuous collaborative efforts are needed for TWSL to develop into a superior and competitive environmental education tourism destination. Keywords : TWSL, planning strategy, educational tourism, environmental management, sustainable tourism